A COMPARATIVE STUDY ON THE EFFICACY OF PRAPOUNDARIKADI TAILA AND BHRINGARAJA TAILA NASYA AND SHIROABYANGA ALONG WITH DHATRITILADIYOGA INTERNALLY IN AKALA PALITHYA (AYUSHDHARA, 2017)
Skin and hair color have been at the center of attention of humans since ancient times. Premature greying is an important cause of low self-esteem, often interfering with socio-cultural adjustment. And it is a burning problem as large percent of population especially young men and women in present times are suffering. In Ayurveda premature graying of hair is called as Akalapalitya. The incidence of premature ageing along with Akala Palitya is on increase, particularly in tropical and developing countries. According to W.H.O in India, its incidence is high in the age group of 20-30 years. Hence premature graying has long attracted researchers and industry alike with scientific as well as commercial targets. Hair coloring involves the use of chemicals which can result in a range of adverse effects like allergic reaction. Yet, apart from various hair dyes of varying efficacy and duration, fully satisfactory solutions for the graying problem remain to be brought to market.In this study, Prapoundarikaditaila and Bhringarajataila was taken for Nasya and Shiroabhyanga which has been mentioned in classics for Urdhwajathrugata Rogas and Palithya. Also Dhatritiladiyoga having Rasayana property helps in blackening of hair told by Acharya Yogarathnakara. In the present study 40 diagnosed Akala Palithya cases were divided into two groups of 20 each. Group A was treated by Prapoundarikaditaila Prathimarsha Nasya and Shiroabyanga along with Dhatritiladiyoga internally twice daily for 90 days. Group B was treated by Bhringarajataila Prathimarsha Nasya and Shiroabyanga along with Dhatritiladiyoga internally twice daily for 90 days. In the present study it was observed that Group A showed better results compared to that of Group B.